Tau imaging detects distinctive distribution of tau pathology in ALS/PDC on the Kii Peninsula. (8th January 2019) - Shinotoh, Hitoshi; Shimada, Hitoshi; Kokubo, Yasumasa; Tagai, Kenji; Niwa, Fumitoshi; Kitamura, Soichiro; Endo, Hironobu; Ono, Maiko; Kimura, Yasuyuki; Hirano, Shigeki; Mimuro, Maya; Ichise, Masanori; et al.
Abstract : Objective: To characterize the distribution of tau pathology in patients with amyotrophic lateral sclerosis/parkinsonism dementia complex on the Kii Peninsula (Kii ALS/PDC) by tau PET using [ 11 C]PBB3 as ligand. Methods: This is a cross-sectional study of 5 patients with ALS/PDC and one asymptomatic participant with a dense family history of ALS/PDC from the Kii Peninsula who took part in this study. All were men, and their age was 76 ± 8 (mean ± SD) years. Thirteen healthy men (69 ± 6 years) participated as healthy controls (HCs). Dynamic PET scans were performed following injection of [ 11 C]PBB3, and parametric PET images were generated by voxel-by-voxel calculation of binding potential ( BP* ND ) using a multilinear reference tissue model. [ 11 C] Pittsburgh compound B (PiB) PET, MRI, and cognitive tests were also performed. Results: A voxel-based comparison of [ 11 C]PBB3 BP* ND illustrated PET-detectable tau deposition in the cerebral cortex and white matter, and pontine basis including the corticospinal tract in Kii ALS/PDC patients compared with HCs (uncorrected p < 0.05). Group-wise volume of interest analysis of [ 11 C]PBB3 BP* ND images showed increased BP* ND in the hippocampus and in frontal and parietal white matters of Kii ALS/PDC patients relative to HCs ( p < 0.05, Holm-Sidak multiple comparisons test). BP* ND in frontal, temporal, and parietal gray matters correlated with Mini-Mental State Examination scores in Kii ALS/PDC patients ( p < 0.05). All Kii ALS/PDC patients were negative for [ 11 C]PiB (β-amyloid) except one with marginal positivity. Conclusion: [ 11 C]PBB3 PET visualized the characteristic topography of tau pathology in Kii ALS/PDC, corresponding to clinical phenotypes of this disease.